RANCANG BANGUN MINDSTORM EV3 UNTUK ROBOT PELAYAN MENGGUNAKAN SENSOR ULTRASONIC DAN SENSOR WARNA (STUDI KASUS: SMK RICARDO AUTO MACHINE TANGERANG) - Fadly Ariadi; Tio Andrian (PT Triputra Sejahtera Prima, 2023)
Applications the development of the world of robots and automation is also based on the limitations of human power that cannot work continuously, making humans think of doing automation in carrying out tasks that are usually done by humans. Apart from that, automation is also expected to increase the efficiency of using human resources, reduce work errors and reduce operational costs that must be incurred. Automation that can be carried out includes the creation of robots that do not know fatigue and are not influenced by emotions at work. This robot functions to help humans in doing tasks. Robots can also reduce work errors that are often made by humans (human error). More focus on service processes in large restaurants or canteens conventionally using human resources. The problem that arises is in terms of efficiency and customer service, we can take advantage of the role of robots to improve customer service and efficiency. On the other hand, when viewed from the customer's point of view, the lack of available human resources makes them have to take a long time to get their orders, not infrequently because there is no system that regulates that queues are missed or even not delivered by the canteen waiter. This is a problem that often occurs and needs further action to overcome these weaknesses or problems. Next, in terms of technology, which is developing rapidly, it is appropriate for schools with a technology base, such as Ricardo Auto Machine Vocational School, to be able to implement robotic and automation systems. From the process and results of this study, this research produces robots that are able to deliver buyer orders properly according to system instructions produced in accordance with the researchers' goals.